Islamization and the Transition of Power in Nusantara According to Kiai Abul Fadhol's Aḥlā al-Musāmarah - Moh. Ashif Fuadi (Islamica: Jurnal Studi Keislaman, 2021)
The discourse on the process of Islamization in Nusantara (Indonesia) still attracts academic attention. This article discusses the history of Islamization in Nusantara as represented by the book of Aḥlā al-Musāmarah written by Kiai Fadhol. He mentions Ten saints (Walisepuluh) as propagators of Islam in Java, adding one to the nine generally known as Walisongo. He also describes that Islam was brought to Nusantara by the scholars (‘ulamā’) from Pasai, who carried da‘wah out through several channels of Islamization. Using the library research method, this article shows no significant difference between the Walisepuluh and the Walisongo characters. The Islamization of Nusantara presented in the book was intensified through the diaspora of kinship marriages, the education of the Pesantren Ampel Denta, which produced a network of students, and the establishment of Demak Kingdom, which strengthened the influence of Islam over the Javanese population.